Lightweight Sandwich Construction. - Davies, J. M. (John Wiley & Sons, 2008)
Sandwich panels are being used increasingly as the cladding of buildings like factories, warehouses, cold stores and retail sheds. This is because they are light in weight, thermally efficient, aesthetically attractive and can be easily handled and erected. However, to date, an authoritative book on the subject was lacking. This new reference work aims to fill that gap. The designer, specifier and manufacturer of sandwich panels all require a great deal of information on a wide range of subjects. This book was written by a group of European experts under the editorship of a UK specialist in li.